Perbedaan Kelembapan Kulit Sebelum dan Sesudah Pemberian Suplemen Kolagen pada Mahasiswi Fakultas Kedokteran di Jakarta: Penelitian - Septiani Wibowo, Jessie; Ekowati, Ana Lucia; Wijaya, Lorettha; Dewi, Kardiana Purnama (Cermin Dunia Kedokteran, 2026)
Introduction: Adequate nutrition, including collagen supplements and the use of moisturizers, can improve skin hydration. This study aims to determine the effects of collagen supplements and several factors such as history of keratosis and atopic dermatitis, sun exposure, bathing habits, and water intake on skin moisture. Methods: This is a descriptive-analytical study with consecutive sampling involving 29 female students aged 19–21 years who met the inclusion and exclusion criteria. The participants were given collagen supplements for 12 weeks, and skin moisture was measured at weeks 0, 4, 8, and 12 using the skin analyzer SK-8 on the upper left arm. Results: This study showed that the average skin moisture level was 32.02% before supplementation and 68.37% after supplementation, indicating a significant difference (p < 0.001). Factors such as history of keratosis and atopic dermatitis, sun exposure, bathing habits, and water intake were not related to skin moisture. Conclusion: These findings suggest that collagen supplementation may contribute to improved skin hydration under the studied conditions.